1999
DOI: 10.1001/jama.282.13.1254
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cyclooxygenase-2 Expression and Colorectal Cancer

Abstract: Our data indicate that COX-2 expression in colorectal cancer may be related to survival. These data add to the growing epidemiological and experimental evidence that COX-2 may play a role in colorectal tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
253
4
12

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(292 citation statements)
references
References 26 publications
19
253
4
12
Order By: Relevance
“…This may reflect the fact that our samples are from a welldefined stage of disease progression, that is, Dukes' C tumours. Previously, it has been suggested that Cox-2 expression is associated with poorer outcomes; however, these studies compared expression across clinical disease stages and were not able to demonstrate any predictive potential independent of Dukes' stage (Sheehan et al, 1999;Masunaga et al, 2000). Patients with a high level of Cox-2 expression in the normal mucosa did seem to have survival advantage.…”
Section: Discussionmentioning
confidence: 94%
“…This may reflect the fact that our samples are from a welldefined stage of disease progression, that is, Dukes' C tumours. Previously, it has been suggested that Cox-2 expression is associated with poorer outcomes; however, these studies compared expression across clinical disease stages and were not able to demonstrate any predictive potential independent of Dukes' stage (Sheehan et al, 1999;Masunaga et al, 2000). Patients with a high level of Cox-2 expression in the normal mucosa did seem to have survival advantage.…”
Section: Discussionmentioning
confidence: 94%
“…These efforts have led to the use of non-steroidal anti-inflammatory drugs (NSAIDS) that target the pro-inflammatory enzyme, COX-2, whose expression is increased in adenomas and colon carcinoma [1][2][3][4][5]. Although these agents have been shown to cause a dosedependent reduction in the size and frequency of intestinal polyps in APC-deficient MIN mice [1,6,7] and in humans harboring the familial adenomatous polyposis (FAP) mutation [8,9], cessation of drug therapy is accompanied by re-emergence of polyps [8] with potential to progress to frank carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Usando apenas carcinomas, resultados semelhantes foram encontrados por Yamauchi et al que também mostraram uma expressão de COX-2 em 71% dos espécimes analisados 15 . Por outro lado, Sheehan et al apresentaram resultados de 100% de expressão, com variação de grau de acordo com o estágio da lesão 14 . A mesma discordância em freqüência pode ocorrer com os adenomas.…”
Section: Expressãounclassified
“…Outro fator que dificulta a avaliação são os escores de positividade, que variam amplamente entre os autores. A maioria adota escores semiquantitativos baseados no percentual de células tumorais imunorreativas, os quais muitas vezes diferem entre os autores 14,15,22 . Em nosso meio Jurach et al encontraram pontos de corte apenas aos 10% quando avaliaram a positividade do p53 no prognóstico de tumores de reto 23 .…”
Section: Expressãounclassified